Controversial Themes in Advertisements: On Manipulating the Emotions of Audiences and Extending the Boundaries of the Social ‘Taboo’ - Małgorzata Koszembar-Wiklik (Communication Today, 2025)
In the modern world, manipulation is being experienced practically every day. Manipulation is an important element of the strategy of communication and advertising in business. A large selection of competitive products and advertising noise make it increasingly difficult for a product to break through to customer awareness. On the one hand, advertising creates consumer attitudes and, on the other hand, the clutter of advertising and promotional announcements forces companies to search for more and more sophisticated ways to get to the customers and attract their attention. Advertisers reach for controversial themes, shocking with carefully selected images. Advertising starts to involve themes that used to be considered social taboos or at least they were the embarrassing ones, intimate or not-discussed openly in many cultures. Advertising functions as a mirror that reflects reality and, at the same time, it can shape the reality. Contemporary advertisements exhibit neutralisation of violence, pornography, attacking religious, and/or social values, often even forming the canon of a given culture. The article addresses the issue of manipulation in advertising. The author points out the phenomenon of manipulation in advertising, giving examples of controversial themes in various commercials and discussing their implications in extending social taboos’ boundaries.